Trem2 regulates macrophage phenotype via the JAK2/STAT3 signaling pathway to ameliorate ventricular remodeling after acute myocardial infarction - Zefeng He; Jing Feng; Ru Yan; Peng Wu; Baozhen Zhu; Huifang Li; Taoyu Yang; Yaxin Lu; Baotong He; Xueping Ma; Shaobin Jia; Guangzhi Cong (Molecular Biology Reports, 2026)

Tracking the role of subducted magnesite in serpentinite to transport incompatible elements into the deep mantle - Yuan-Ru Qu; Hamed Gamaleldien; Tim E. Johnson; Jianfeng Ma; Tamer Abu-Alam; Denis Fougerouse; Steven M. Reddy; Noreen.J. Evans (Lithos, 2026)

The co-ecotoxicity of microplastics and associated contaminants (PFOA) on soil ecosystems - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine; Yi-kai Wang; Jian Su; Jie Chen (Journal of Environmental Chemical Engineering, 2026)

Doping-engineered nanosystem for enhancing the antibacterial efficiency of scaffolds through synergistic aSDT and CDT - Wenjie Ma; Ru Jia; Patiguli Aihemaiti; Houfeng Jiang; Lanlan Dong; Wurikaixi Aiyiti; Cijun Shuai; Chongxian He (Chemical Engineering Journal, 2026)

Synergistic photodynamic and photothermal antibacterial therapy enabled by BSCN heterojunction in PEEK bone implants - Ru Jia; Wenjie Ma; Wurikaixi Aiyiti; Houfeng Jiang; Patiguli Aihemaiti; Lanlan Dong; Cijun Shuai (Chemical Engineering Journal, 2026)

pH-responsive microcapsules co-delivering radioprotectant and probiotics for synergistic mitigation of radiation-induced enteritis - Caifang Gao; Jiaxuan Ma; Luke Ge; Yongle Zhao; Ru Feng; Pengqi Zhu; Jinghua Sun; Ruiping Zhang (Chemical Engineering Journal, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Complete mitochondrial genomes and phylogenetic analysis of three species of Indo-Pacific freshwater gobies, Stiphodon (Gobiiformes, Oxudercidae) - Cheng-He Sun; Xian-Ru Li; Su-Fan Zhou; Yan-Zi Zhong; Xiao Ma; Xiao-Die Chen (Journal of Genetics, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Optimized green extraction of flavonoids from Lycium barbarum leaves using betaine-ethylene glycol NADES: Mechanisms, identification, and bioactivity - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Xin-Yue Zhang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

Mechanisms and effects of ozone-pullulanase treatment on multiscale structures and in vitro digestibility of rice starch - Zixuan Liu; Chunfan Guo; Mingyue Chen; Yaping Xu; Jingxuan Ma; Ru Wang; Zhaoxia Wu (Food Chemistry, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Activation-optimized anti-CD3 valency control enables combinatorial discovery of multi-specific nanoantibodies for solid tumor immunotherapy - Long Zhu; Ya-Jing Ma; Jian-Kang Kang; Xiu-Hai Che; Dong-Kun Zhao; Yin-Yi Cai; Yao-Ru Yu; Song Shen; Jun Wang (Science Bulletin, 2026)

Waste cotton textiles-derived cellulose superhydrophobic aerogel for efficient oil-water separation - Ya-hui Li; Hui-Jiang; Xiao-quan Zhu; Ru-ru Ma; Er-min Zhou; Jun-li Luo; De-qiang Li; Hong-tao Jia; Jun Li; Lu-xiang Wang (Journal of Water Process Engineering, 2026)

A novel sterilization mechanism of cold plasma coupled with low-dose ZnO nanoparticles for food Decontamination: Synergistic reactive species generation and zinc ion release - Hang-Bo Xu; Meng-Ru Du; Zhen Jiao; Pan-Feng Guan; Ruo-Nan Ma (Food Microbiology, 2026)

Microplastics Inhibit Microbial Abundance and Enzyme Activities in Pb/Cd Co-contaminated Soil: The Alleviating Role of Biochar - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine (Journal of Soil Science and Plant Nutrition, 2026)

Enhanced photocatalytic fuel cell performance via C/WO3/ZnFe2O4 ternary photoanode for simultaneous wastewater degradation and energy harvesting - Yi Xiao; Ru Zhang; Qi Feng; Hailong Gao; Jiawei Ma; Ting Wu; Yongkui Huang; Longjun Xu; Chenglun Liu (Journal of Environmental Management, 2026)

Green and efficient extraction of polyphenols from Lycium barbarum leaves using a betaine-based natural deep eutectic solvent: Process optimization, mechanistic elucidation, and bioactivity evaluation - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Jing-Yi Wang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

Zinc isotope insights into the Archean continental crust stabilization: Evidence from potassic granites, Yilgarn and Pilbara cratons - Jianfeng Ma; Hamed Gamaleldien; Yuan-Ru Qu; Robert H. Smithies (Chemical Geology, 2026)

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Iron and zinc isotopic insights into the formation of Archean continental crust - Jianfeng Ma; Hamed Gamaleldien; Robert H. Smithies; Tim Johnson; Yuan-Ru Qu; Sheng-Ao Liu; Christopher L. Kirkland (Earth and Planetary Science Letters, 2026)

Terbium chloride post-treatment for highly efficient and stable Sb2(S,Se)3 solar cells - Shengquan Shan; Jihao Ma; Yang Chen; Lun Zhang; Chengyang Wang; Yanrui Yang; Ru Zhou; Mei Lyu; Jun Zhu (Chemical Engineering Journal, 2026)

Enhancing camptothecin biosynthesis in Camptotheca acuminata through CrLAMT transfer from Catharanthus roseus - Ru Huang; Wen-Hui Ma; Bing-Run Yang; Fang Yu; Ping Kou (Biotechnology Letters, 2026)

Determining the age and size at sexual maturity in the sea cucumber Apostichopus japonicus - Siyi Yan; Zhaoyang Ma; Xiangyue Li; Xianjie Sui; Beini Deng; Jiaze Wang; Libin Zhang; Xiaoshang Ru (Aquaculture International, 2026)

Size-dependent shear behavior of backfill–rock interfaces constructed from in-situ 3D morphology: experimental and numerical study - Wenkai Ru; Diyuan Li; Hiroyuki Noda; Hao Gong; Pingkuang Luo; Jinyin Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Editor's note “Silica nanoparticles promoted pro-inflammatory macrophage and foam cell transformation via ROS/PPAR/NF-B signaling” [Sci. Total Enviro. 881 (2023) 163430] - Caixia Guo; Xinying Zhao; Ru Ma; Lingnan Zhu; Yueyue Chen; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2026)

Molecular identification and genetic diversity of Echinococcus granulosus sensu stricto in livestock from Qinghai lake on the Qinghai-Tibetan plateau - Jun He; Guoyan Zhou; Fan Zhang; Hongrun Ge; Ao Chen; Ru Meng; Zhihong Guo; Yijuan Ma; Yong Fu (Veterinary Research Communications, 2026)

Size Effects on Backfill–Rock Interface Shear Behavior: Insights from Multi-method Modeling - Wenkai Ru; Jinyin Ma; Hiroyuki Noda; Diyuan Li; Hao Gong; Junjie Zhao; Zhen Li (Rock Mechanics and Rock Engineering, 2026)

Recent understanding of crosstalk between muscle and different organs in regulating freshwater fish flesh quality under stress condition: A review - Liwen Wu; Liangzi Zhang; Ling Peng; Yong Long; Guili Song; Soottawat Benjakul; Juan You; Ru Liu; Qilin Huang; Huawei Ma; Dan Jia; Tao Yin (Aquaculture, 2026)

Preparation of indicator cards for freshness detection of rice with four different processing degrees during storage based on olfactory visualization technology - Wan-ru Liu; Yang Yang; Yue Xu; Bing Wang; Guang Zhang; Xin-yu Xu; Yuan-yuan Wang; Chun-min Ma; Na Zhang (Food Chemistry, 2026)

Parental exposure to phenanthrene induces thyroid disruption in zebrafish offspring - Liqiao Zhong; Fengyue Zhu; Luyin Wu; Baoshan Ma; Huijun Ru; Xinbin Duan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Tracking the dynamic changes in vegetation belts in China: spatiotemporal insights into climate and human influences - Yong Xu; Yun-Gui Lu; Qiang-Yu Dai; Wen-Ting Huang; Shang-Chen Zhou; Ru-Long Ma; Wen-Qiang Peng; Yu-Xi Feng (Regional Environmental Change, 2026)

Research progress on chemical constituents and biological activities of medicinal plants from Euonymus genus - Ying-Jun Ma; Xin-Ru Li; Meng-Qi Gao; Jia-Jia Liu; Ammara Khalid; Jie-Ting Chen; Fan-Cheng Meng (Natural Product Research, 2026)

Tailoring hydrophilic channels size in multiblock poly(aryl alkyl) membranes for anion exchange membrane water electrolysis - Xuejiao Dong; Weiwei Luan; Yixiang Ma; Minglong He; Bin Wu; Jibin Miao; Ru Xia; Jiasheng Qian; Guangzu Wang; Qianqian Ge (Desalination, 2026)

Dual-modal antioxidant nanozyme hydrogel for protection against noise-induced hearing loss via attenuation of oxidative stress and NF-κB/MAPK signaling - Liang Xia; Ru Tang; Yi Chen; Ning Ma; Lili Xiao; Xiaoyan Chen; Xiaoyin Mao; Keyi Li; Yanmei Feng; Jingjing Liu; Amin Zhang (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

Strength enhancement and microstructural observation of cement-stabilized calcareous sand by optimizing the preparation process - Weishen Li; Yang Wu; Xue Li; Han Ma; Yifei Ru; Xiangxing Ye (Journal of Cleaner Production, 2026)

Reducing the healthcare carbon footprint through fully self-service artificial intelligence-powered screening: A comparative simulation study utilizing data from Shanghai City and Lixin Town, China - Yingyan Ma; Xiyuan Shi; Lina Lu; Yi Xu; Juzhao Zhang; Tao Yu; Yajun Peng; Enren Ke; Senlin Lin; Ru Guo; Haidong Zou (Journal of Cleaner Production, 2026)

Effects of nighttime warming and nitrogen addition on phytoplankton biomass in a submerged macrophytes-dominated freshwater wetland - Yaru Lyu; Jiayin Feng; Wenjing Ma; Chao Wang; Mengyu Yan; Zixuan Yang; Yunpeng Guo; Jinhua Zhang; Hongpeng Wang; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Journal of Environmental Sciences, 2026)

Soil respiration and its temperature sensitivity on croplands in response to biotic and abiotic factors under straw and nitrogen fertilizer management - Ru Guo; Ruixuan Hao; Xiaoyi Yang; Rui Qian; Zijun Ma; Yunyun Yang; Peng Zhang; Zhikuan Jia; Yuncheng Liao; Xiaolong Ren; Xiaoli Chen (CATENA, 2026)

Adsorption of Methylene Blue using Poly(N-vinylpyrrolidone)-Graphene Oxide Composite: Kinetics, Equilibrium, Thermodynamics, and Mechanisms - Xiaoya Li; Ru Zheng; Guangyu Duan; Zhanfang Cao; Kai Han; Hong Zhong; Xin Ma; Shuai Wang (Water, Air, & Soil Pollution, 2026)

Performance and toxicity assessment of photocatalytic degradation of sulfanilamide by g-C3N4 nanosheets constructed using temperature gradient regulated etching - Yujie Jiao; Yaqi Mao; Fei Fu; Yongxia Ma; Ru Li; Qikai Liu; Jiali Lei; Sujin Lu; Yang Liu (Environmental Research, 2025)

Antibiotics, antibiotic resistance genes, and environmental drivers: Assessment of resistance pollution along the Yangtze River Basin - Chengcheng Bu; Chong Chen; Weiwei Zhang; Ru Zhang; Jinpeng Yu; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Yuefei Ruan; Limin Ma (Environmental Pollution, 2025)

Hydrophobic surface modified calcium alginate fibers for preparing flame retardant and comfortable Janus fabrics - Yue Ma; Zihan Wu; Meijie Qu; Ru Chen; Jing Guo; Yuezhen Bin (Carbohydrate Polymers, 2025)

DPP4, a potential tumor biomarker, and tumor therapeutic target: review - Lu Sun; Yuhui Ma; Chenchen Geng; Xiaoqian Gao; Xinbing Li; Qi Ru; Shuzhen Zhu; Ping Zhang (Molecular Biology Reports, 2025)

Balanced Source-Sink Strength in Optimized Cultivation Management of Wheat Could Coordinate High Yield and High Nitrogen Use Efficiency - Juan Kang; Yingying Chu; Jiaxin Zhao; Geng Ma; Haiyan Zhang; Yanfei Zhang; Guozhang Kang; Guangxin Ru; Dongyun Ma; Yingxin Xie; Chenyang Wang (International Journal of Plant Production, 2025)

A nonlocal strain gradient higher-order beam theory and its application to wave propagation in radially graded nanotubes - Wei-Li Ma; Peng-Yu Wang; Hui-Ru Cui; Xian-Fang Li (Ocean Engineering, 2025)

Machine learning-enhanced prediction of size-resolved gas-particle partitioning quotient: Implication for health risk assessment of polycyclic aromatic hydrocarbons - De-Qi Wang; Wan-Li Ma; Ru-Peng Wang; Pu-Fei Yang; Peng-Tuan Hu; Shi-Ming Jia; Meng Qin (Journal of Hazardous Materials, 2025)

Insights into the synergistic cross-linking effect of EGCG and TGase on surimi gels - Qin Yang; Jinling Li; Wentao Ma; Ru Liu; Shengbi Zou; Yongqiang Zhao; Shanbai Xiong; Jianhua Rong; Yang Hu (Food Chemistry, 2025)

Foam dust suppressant based on synergistic coordination between oxidized starch-gelatin Schiff base reaction and multiple crosslinking - Xinyue Zhang; Ru Wang; Haiming Yu; Jiayin Wang; Haochun Ma (Carbohydrate Polymers, 2025)

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Hydrological variations dominate long-term ecological dynamics in a large alpine Lake Issyk-Kul, arid Central Asia: Evidence from sediment multi-biomarker analyses - Hongliang Zhang; Jinglu Wu; Ru Guo; Miao Jin; Long Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Salicylic acid promotes arsenic uptake in Pteris vittata via regulation of key genes and elevated nitric oxide and spermidine - Zhi-Hua Dai; Ze-Chao Li; Xi Chen; Ru Huang; Jian-Hua Sun; Chen-Jing Liu; Lena Q. Ma; Ru-Yi Yang (Journal of Hazardous Materials, 2025)

Effect of multiscale interface roughness on shear behavior of backfill-rock specimen - Wenkai Ru; Diyuan Li; Zhenyu Han; Hao Gong; Jinyin Ma (International Journal of Rock Mechanics and Mining Sciences, 2025)

Iron and zinc isotopes constrain the continental crust formation - Jianfeng Ma; Hamed Gamaleldien; Sheng-Ao Liu; Yuan-Ru Qu (Geochimica et Cosmochimica Acta, 2025)

The threat of microplastics to human kidney health: Mechanisms of nephrotoxicity and future research directions - Ru-Yu Tan; Qin-Ying She; Yun-Ci Ma; Ming-Hong Liu; Li-Juan Li; Li-Li Huang; Yi-Wen Zhong; Hui-Xin Bi (Environmental Research, 2025)

Polyphenol-synthesized nanoparticles with ALDH3A1 delivery ability for activating estrogen signaling for diabetic wound healing - Xiaoxuan Ma; Yiqiong Liu; Jingsi Jiang; Yi Ru; Ying Luo; Jiankun Song; Zhan Zhang; Ying Zhang; Dan Yang; Haotian Xu; Haiqing Dong; Yongyong Li; et al. (Chemical Engineering Journal, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Molecular characterization and optical properties of methanol-soluble brown carbon chromophores in a metropolitan area of northeastern Asia - Yu-Chieh Ting; Yi-Ru Ko; Yueh-Ling Hung; Cheng-Hua Ma; Cheng-Chih Hsu; Yu-Hsiang Cheng (Science of The Total Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Covalent binding of vitamin K3 photosensitizers to nanofibrous membranes for daylight-driven antimicrobial applications - Yibo Ru; Qingli Dong; Kexin Li; Xinyi Zhao; Lang Yan; Xiang Wang; Yangtai Liu; Yue Ma (Chemical Engineering Journal, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Microbial life-history strategies mediate temperature effects on organic carbon pools in black soils - Lihui Lyu; Chaoqun Wang; Kunkun Fan; Jiasui Li; Teng Yang; Guifeng Gao; Ru Sun; Jiao Wang; Xiyuan Xu; Yuxiao Zhang; Yuying Ma; Jiabao Zhang; et al. (Soil Ecology Letters, 2025)

Spatial distribution, phase partitioning, and ecological risk assessment of typical pesticides in Yangtze River Basin - Chengcheng Bu; Chong Chen; Xitong Fu; Weiwei Zhang; Ru Zhang; Yu Hua; Ruolan Jia; Yuefei Ruan; Kenneth Mei Yee Leung; Limin Ma (Journal of Hazardous Materials, 2025)

Different responses of phytoplankton taxa to water N and P inputs in a freshwater wetland: A mesocosm study - Wenjing Ma; Jiayin Feng; Jinhua Zhang; Hongpeng Wang; Yunpeng Guo; Yaru Lyu; Chao Wang; Zixuan Yang; Mengyu Yan; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Marine Pollution Bulletin, 2025)

Systematic review of natural coumarins in plants (2019–2024): Chemical structures and pharmacological activities - Ze-Dong Nan; Ying Shang; Yi-Dong Zhu; Hui Zhang; Ru-Ru Sun; Jing-Jing Tian; Zhi-Bo Jiang; Xiao-Li Ma; Changcai Bai (Phytochemistry, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Comprehensive molecular biology and metabolomics analysis reveal the changes on muscle quality of Megalobrama amblycephala exposure to ammonia nitrogen during transportation - Ling Peng; Ziaur Rahman; Yuanyong Tian; Tao Yin; Shanbai Xiong; Juan You; Ru Liu; Lan Wang; Qilin Huang; Huawei Ma (Food Research International, 2025)

Schiff base crosslinking based dialdehyde-chitosan/gelatin/tea polyphenol electrospun nanofibrous membranes with excellent antibacterial and antioxidant activity for food packaging - Yu Ma; Ru Tian; Yudong Song; Mengxiao Liu; Jie Li; Zhichun Bi; Hui Huang; Yongxin Li (Food Packaging and Shelf Life, 2025)

Effects of modified KGM on the gelling capability of fish protein: Novel insights into hooking effect - Ziaur Rahman; Sijin Zhang; Arsalan Khan; Juan You; Ru Liu; Qilin Huang; Huawei Ma; Soottawat Benjakul; Tao Yin (Food Chemistry, 2025)

Efficient catalyst-free CO2 reduction by CO2— radical anions at gas–liquid interface under ambient conditions - Nannan Liu; Qinglong Ru; Wei Jiang; Hui Hu; Yongcui Yang; Kailan Ma; Zuliang Du; Yu Jia; Xiaojing Yang; Bao Zhang; Gang Cheng (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Functional analysis of Ophraella communa Lesage OcomOBP11 in recognition of Ambrosia artemisiifolia L. volatiles - Yang Yue; Chao Ma; Yan Zhang; Wei-hua Ma; Jing-jing Wang; Zhen-ya Tian; Guang-mei Chen; Ru-wen Li; Jin-hua Li; Jing-fang Yang; Zhong-shi Zhou (Pesticide Biochemistry and Physiology, 2025)

Electrospun nanofiber membranes based on dialdehyde pullulan polysaccharide and schiff base crosslinked lysozyme for antibacterial packaging of blueberries - Yu Ma; Ru Tian; Yudong Song; Chenghui Yin; Hui Huang; Yongxin Li (Food Bioscience, 2025)

Electrochemically enhanced micro-electrolytic ceramic substrate infiltration system as an efficient approach for treatment of imidacloprid wastewater - Ru Zhang; Weiwei Zhang; Chengcheng Bu; Guangyao Chen; Shuyun Li; Yuchen Han; Haibin Ma; Anyong Xu; Desheng Wang; Limin Ma (Environmental Monitoring and Assessment, 2025)

Molecular mechanisms of ascorbic acid affected by ozone in fresh-cut kiwifruit: Insights from salicylic acid synthesis and signal transduction - Yajing Wang; Jingxuan Ma; Tianyu Wang; Liyan Rong; Yingqi Zhao; Shuyue Zhang; Zixuan Liu; Ru Wang; Zhaoxia Wu (Postharvest Biology and Technology, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

A 200-year record of polycyclic aromatic hydrocarbon (PAH) deposition in Lake Balkhash, arid Central Asia: PAH sources and inferred human history - Ru Guo; Jinglu Wu; Miao Jin; HongLiang Zhang; Long Ma (Journal of Paleolimnology, 2025)

Endophytes and soil microorganisms participate in the germination of Sinojackia xylocarpa Hu by degrading the pericarp - Zi-Hao Li; Xin-Yi Ma; Huan Yang; Run-Guo Zang; Jia-Ru Li (Acta Physiologiae Plantarum, 2025)

Sediment Provenance and Facies Analysis of the Huagang Formation in the Y-Area of the Central Anticlinal Zone, Xihu Sag, East China Sea - Xiao Ma; Wei Yan; Yi Yang; Ru Sun; Yue Chao; Guoqing Zhang; Chao Yang; Shudi Zhang; Dapeng Su; Guangxue Zhang; Hong Xu (Journal of Marine Science and Engineering, 2025)
Recent breakthrough exploration wells in the Huagang Formation in the Y-area of the central anticlinal zone of the Xihu Sag have confirmed the significant exploration potential of structure–lithology complex hydrocarbon reservoirs. However, limited understanding of the provenance system, sedimentary facies, and microfacies has hindered further progress in complex hydrocarbon exploration. Analysis of high-precision stratigraphic sequences and seismic facies data, mudstone core color, grain-size probability cumulative curves, core facies, well logging facies, lithic type, the heavy-mineral ZTR index, and conglomerate combinations in drilling sands reveals characteristics of the source sink system and provenance direction. The Huagang Formation in the Y-area represents an overall continental fluvial delta sedimentary system that evolved from a braided river delta front deposit into a meandering river channel large-scale river deposit. The results indicate that the primary provenance of the Huagang Formation in the Y-area of the Xihu Sag is the long-axis provenance of the Hupi Reef bulge in the northeast, with supplementary input from the short-axis provenance of the western reef bulge. Geochemical analysis of wells F1, F3, and G in the study area suggests that the prevailing sedimentary environment during the period under investigation was characterized by anoxic conditions in nearshore shallow waters. This confirms previous research indicating strong tectonic reversal in the northeast and a small thickness of the central sand body unrelated to the flank slope provenance system. The aforementioned findings deviate from conventional understanding and will serve as a valuable point of reference for future breakthroughs in exploration.

Effect of cinnamaldehyde and tannic acid nano-emulsions on meat quality and protein oxidation during cold storage - Ramy M. Khoder; Xinqun Deng; Liangzi Zhang; Qilin Huang; Juan You; Ru Liu; Huawei Ma; Tao Yin (Food Packaging and Shelf Life, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Nano fish bone prepared by high-energy media milling extends the shelf life of tofu during cold storage: Unlocking the restriction on water mobility - Ramy M. Khoder; Liangzi Zhang; Qilin Huang; Juan You; Huawei Ma; Tao Yin; Ru Liu (Food Chemistry, 2025)

Differentiation revelation of wine quality induced by maceration technology under the mediation of environmental factors and microbial community - Manman Gao; Shuo Yu; Jianing Bai; Ru Chen; Yunjie Li; Liping Du; Lijuan Ma; Huiling Zhang; Xiaoju Tian (Food Bioscience, 2025)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Effects of temperature, relative humidity and soil organic carbon content on soil-air partitioning coefficients of volatile PFAS - Weiwei Zhang; Limin Ma; Songsong Chen; Chong Chen; Chengcheng Bu; Jinpeng Yu; Ru Zhang; Yongzhi Wang; Haoyu Zeng; Yuchen Han (Science of The Total Environment, 2024)

The soil-air interfacial migration process of volatile PFAS at the contaminated sites: Evidence from stable carbon isotopes with CSIA - Zhang Weiwei; Chen Songsong; Wang Yongzhi; Zhang Ru; Bu Chengcheng; Yu Jinpeng; Ma Limin (Environmental Pollution, 2024)

Advanced growing-season precipitation peak promotes soil nitrogen mineralization in a semi-arid grassland - Jiayin Feng; Xiaojing Yue; Benqing Li; Jingyi Ru; Zhenxing Zhou; Lingjie Kong; Jiajun Zhang; Jiaxin Zhou; Guilin Zhou; Wenjing Ma; Yaru Lyu; Jian Song; et al. (CATENA, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Experimental study on the influence of particle morphology on compression characteristics of coral sand in South China Sea - Ru Qu; Cheng-hao Ma; Chang-qi Zhu; Hai-feng Liu (Ocean Engineering, 2024)

Does artificial intelligence affect the ecological footprint? –Evidence from 30 provinces in China - Yong Wang; Ru Zhang; Kainan Yao; Xuejiao Ma (Journal of Environmental Management, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Changes in plant litter and root carbon inputs alter soil respiration in three different forests of a climate transitional region - Jiayin Feng; Chunyu Wang; Jingjing Gao; Huixia Ma; Zheng Li; Yuanfeng Hao; Xueli Qiu; Jingyi Ru; Jian Song; Shiqiang Wan (Agricultural and Forest Meteorology, 2024)

Corrigendum to “CLAUDIN7 modulates trophectoderm barrier function to maintain blastocyst development in pigs” [Theriogenology 158 (2020) 346–357 10.1016/j.theriogenology.2020.09.038] - Di Gao; Tengteng Xu; Xin Qi; Wei Ning; Shang Ren; Zhenyuan Ru; Kaiyuan Ji; Yangyang Ma; Tong Yu; Yunsheng Li; Zubing Cao; Yunhai Zhang (Theriogenology, 2024)

Insight into the mechanism on nano fish bone improving the quality of marinated snakehead fish slices during freeze-thaw cycles - Ziaur Rahman; Tao Yin; Ramy M. Khoder; Abroo Tabasum; Qilin Huang; Juan You; Huawei Ma; Ru Liu; Shanbai Xiong (Innovative Food Science & Emerging Technologies, 2024)

Identification and fine mapping of a QTL-rich region for yield- and quality-related traits on chromosome 4BS in common wheat (Triticum aestivum L.) - Jinghui Li; Huanhuan Zhao; Minghu Zhang; Chan Bi; Xiaoyuan Yang; Xintian Shi; Chaojie Xie; Baoyun Li; Guangbin Ma; Zhengang Ru; Tiezhu Hu; Mingshan You (Theoretical and Applied Genetics, 2024)

Sodium Selenite Ameliorates Silver Nanoparticles Induced Vascular Endothelial Cytotoxic Injury by Antioxidative Properties and Suppressing Inflammation Through Activating the Nrf2 Signaling Pathway - Yunyun Ma; Lei Wang; Jing He; Xueping Ma; Jingjing Wang; Ru Yan; Wanrui Ma; Huiyan Ma; Yajuan Liu; Hongqian Sun; Xiaoxia Zhang; Shaobin Jia; et al. (Biological Trace Element Research, 2024)
Silver nanoparticles (AgNP) are the dominant nanomaterials in commercial products and the medical field, but the widespread occurrence of AgNP has become a global threat to human health. Growing studies indicate that AgNP exposure can induce vascular endothelial toxicity by excessive oxidative stress and inflammation, which is closely related to cardiovascular disease (CVD), but the potential intrinsic mechanism remains poorly elucidated. Thus, it has been crucial to control the toxicological effects of AgNP in order to improve their safety and increase the outcome of their applications. Multiple researches have demonstrated that sodium selenite (Se) possesses the capability to counteract the toxicity of AgNP, but the functional role of Se in AgNP-induced CVD is largely unexplored. The aim of this study was to explore the potential protective effect of Se on AgNP-induced vascular endothelial lesion and elucidate the underlying mechanisms. An in vivo model of toxicity in animals was established by the instillation of 200 µL of AgNP into the trachea of rats both with (0.2 mg/kg/day) and without Se treated. In vitro experiments, human umbilical vein endothelial cells (HUVECs) were incubated with AgNP (0.3 µg/mL ) and Se for a duration of 24 h. Utilizing transmission electron microscopy, we observed that the internalization of AgNP-induced endothelial cells was desquamated from the internal elastic lamina, the endoplasmic reticulum was dilated, and the medullary vesicle formed. Se treatment reduced the levels of vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1), inhibited the release of pro-inflammatory cytokines (specifically tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6), improved endothelial cell permeability, integrity, and dysfunction, and prevented damage to the aortic endothelium caused by AgNP. Importantly, we found that Se showed the capacity against AgNP with biological functions in guiding the intracellular reactive oxygen species (ROS) scavenging and meanwhile exhibiting anti-inflammation effects. Se supplementation decreased the intracellular ROS release and suppressed NOD-like receptor protein 3 (NLRP3) and nuclear factor kappa-B (NF-κB) mediated inflammation within AgNP-intoxicated rats and HUVECs. The anti-oxidant stress and anti-inflammatory effects of Se were at least partly dependent on nuclear factor erythroid 2-related factor 2 (Nrf2). Overall, our results indicated that the protectiveness of Se against AgNP-induced vascular endothelial toxicity injury was at least attributed to the inhibition of oxidative ROS and pro-inflammatory NF-κB/NLRP3 inflammasome by activating the Nrf2 and antioxidant enzyme (HO-1) signal pathway.

Pollution level and ecological risk assessment of triazine herbicides in Laizhou Bay and derivation of seawater quality criteria - Zhenzhong Zhang; Yongliang Feng; Weizhong Wang; Shaoguo Ru; Lingchao Zhao; Yuanqing Ma; Xiukai Song; Lijuan Liu; Jun Wang (Journal of Hazardous Materials, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Additive effects of N addition and changing precipitation on soil respiration in a climate transitional forest - Jiayin Feng; Jingjing Gao; Huixia Ma; Chunyu Wang; Yuanfeng Hao; Zheng Li; Jingru Zou; Xueli Qiu; Jingyi Ru; Jian Song; Shiqiang Wan (CATENA, 2024)

Enhancing Infiltration System Via Iron-Carbon Micro-Electrolysis Combined With Electrochemical Intensification: Efficiency And Mechanisms Of Nitrogen And Phosphorus Removal - Guangyao Chen; Limin Ma; Ru Zhang; Chengcheng Bu; Weiwei Zhang; Mudi Zhai; Kyari Umar Dunoma (Water, Air, & Soil Pollution, 2024)

Effect of heating treatment on processing characteristics of rice dough - Wan-ru Liu; Chun-min Ma; Yang Yang; Bing Wang; Xiao-fei Liu; Yan Wang; Xin Bian; Xiao-xue Guo; Guang Zhang; Na Zhang (Innovative Food Science & Emerging Technologies, 2024)

Long-term dynamics of organic matter inputs in sediments of Lake Balkhash, arid Central Asia: Coupled climate and anthropogenic influences - Hongliang Zhang; Jinglu Wu; Ru Guo; Long Ma (CATENA, 2024)

Asperidulins A and B, two new prenylxanthone derivatives from an apple-derived fungus Aspergillus nidulans KIB-HACM-01 - Peng Lai; Li Wang; Chenjie Deng; Yixin Xu; Xiao-Yan Ma; Chun-Ru Cheng; Sheng-Xiong Huang (Natural Product Research, 2024)

Carbon-in-carbon: Hybrid carbonized nanomaterials with multifunctional activities for the treatment of endophthalmitis - Hong-Jyuan Jian; Yi-Ru Chiou; Anisha Anand; Chien-Fu Chen; David Hui-Kang Ma; Jui-Yang Lai; Chih-Ching Huang; Huan-Tsung Chang (Chemical Engineering Journal, 2024)

Screening of Strain from Reconstituted Sheet Tobacco Making High-Yield Enzyme and Aroma - Chun-Xue Yang; Deng Zhang; Hui Ma; Xiao-Meng Guo; Na Yan; Xue-Ting Deng; Xiang-Ru Liao; Zheng-Bing Guan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

The first record of the Gondwanan seed fern Dicroidium Gothan in Laurasia - Yanqi Sun; Shenghui Deng; Yuanzheng Lu; Ru Fan; Xueying Ma; Dan Lyu (Review of Palaeobotany and Palynology, 2024)

Synthesis and adsorption performance of carboxyl-functionalized magnetic agarose gel microspheres for Cu(II) removal - Mingze Ma; Guanglin Liang; Yi Ru; Jun Chen; Yonghui Zhang; Huifen Weng; Anfeng Xiao; Qiong Xiao (Journal of Environmental Chemical Engineering, 2024)

Candidate gene mining of GA-mediated regulation of pear fruit shape - Zeyu Xue; Ru Yang; Yadong Wang; Yuchen Ma; Yujing Lin; Zhengao Li; Yuqin Song; Xinxin Feng; Liulin Li (Horticulture, Environment, and Biotechnology, 2024)

Nighttime warming and nitrogen addition effects on the microclimate of a freshwater wetland dominated by Phragmites australis - Yunpeng Guo; Jian Song; Jiayin Feng; Hongpeng Wang; Jinhua Zhang; Jingyi Ru; Xiaopan Wang; Xu Han; Huixia Ma; Yaru Lyu; Wenjing Ma; Chao Wang; et al. (Science of The Total Environment, 2024)

Edible antimicrobial yeast-based coating with basil essential oil for enhanced food safety - Yibo Ru; Yuqi Zhu; Xiang Wang; Qingli Dong; Yue Ma (Innovative Food Science & Emerging Technologies, 2024)

High-Performance enrichment and sensitive analysis of bisphenol and its analogues in water and milk using a novel Ni-Based cationic Metal-Organic framework - Jin-Yan Ma; Hai-Long Jiang; Fu-Shuai Kang; Lu Liu; Xia Wang; Ru-Song Zhao (Food Chemistry, 2024)

Di (2-ethylhexyl) phthalate induced lipophagy-related renal ferroptosis in quail (Coturnix japonica) - Yu Zhu; Xiang-Yu Ma; Ling-Ge Cui; Ya-Ru Xu; Chen-Xi Li; Milton Talukder; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Proteomics revealed composition- and size-related regulators for hepatic impairments induced by silica nanoparticles - Xinying Zhao; Ru Ma; Alimire Abulikemu; Yi Qi; Xiaoying Liu; Ji Wang; Kun Xu; Caixia Guo; Yanbo Li (Science of The Total Environment, 2024)

Construction of self-assembled nano cellulose crystals/chitosan nanobubbles composite hydrogel with improved gallic acid release property - Miral Javed; Hao Huang; Yueran Ma; Fatima-ezzahra Ettoumi; Lei Wang; Yanqun Xu; Hesham R. El-Seedi; Qiaomei Ru; Zisheng Luo (Food Chemistry, 2024)

Carbon tax and low-carbon credit: Which policy is more beneficial to the capital-constrained manufacturer's remanufacturing activities? - Zhan-Jie Wang; Ru-Fu Zhou; Yong-Feng Ma; Yong-Jian Wang (Environmental Research, 2024)

Optimizing maize productivity: A sustainable approach integrating straw derivatives and film mulching in rainfed agriculture - Rui Qian; Zijun Ma; Yunyun Yang; Ru Guo; Fei Han; Jinjin Wang; Xiaoling Wang; Baoping Sun; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Field Crops Research, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Integrated transcriptome and metabolome analysis revealed that HaMYB1 modulates anthocyanin accumulation to deepen sunflower flower color - Siqi Ma; Hanlin Zhou; Tingting Ren; Er-ru Yu; Bin Feng; Juying Wang; Chengsheng Zhang; Chao Zhou; Yiqiang Li (Plant Cell Reports, 2024)
Key message HanMYB1 was found to play positive roles in the modulation of anthocyanins metabolism based on the integrative analysis of different color cultivars and the related molecular genetic analyses. Abstract As a high value ornamental and edible crop with various colors, sunflowers ( Helianthus annuus L.) provide an ideal system to understand the formation of flower color. Anthocyanins are major pigments in higher plants, which is associated with development of flower colors and ability of oxidation resistance. Here, we performed an integrative analysis of the transcriptome and flavonoid metabolome in five sunflower cultivars with different flower colors. According to differentially expressed genes and differentially accumulated flavonoids, these cultivars could be grouped into yellow and red. The results showed that more anthocyanins were accumulated in the red group flowers, especially the chrysanthemin. Some anthocyanins biosynthesis-related genes like UFGT (UDP-glycose flavonoid glycosyltransferase) also expressed more in the red group flowers. A MYB transcriptional factor, HanMYB1, was found to play vital positive roles in the modulation of anthocyanins metabolism by the integrative analysis. Overexpressed HanMYB1 in tobacco could deepen the flower color, increase the accumulation of anthocyanins and directly active the express of UFGT genes. Our findings indicated that the MYB transcriptional factors provide new insight into the dynamic regulation of the anthocyanin biosynthesis in facilitating sunflower color formation and anthocyanin accumulation.

Desynchronization of neural networks induced by transcranial magneto-acoustical stimulation: a modeling study - Zhenfang Ma; Yuhui Yang; Jianyang Xu; Yi Ru; Yu Yin (Neurophysiology, 2024)

Morpho-physio-biochemical, molecular, and phytoremedial responses of plants to red, blue, and green light: a review - Muzammal Rehman; Jiao Pan; Samavia Mubeen; Wenyue Ma; Dengjie Luo; Shan Cao; Wajid Saeed; Gang Jin; Ru Li; Tao Chen; Peng Chen (Environmental Science and Pollution Research, 2024)

Silver nanoparticles induce endothelial cytotoxicity through ROS-mediated mitochondria-lysosome damage and autophagy perturbation: The protective role of N-acetylcysteine - Jing He; Yunyun Ma; Xudong Niu; Jiansheng Pei; Ru Yan; Fangjing Xu; Jing Ma; Xiaojuan Ma; Shaobin Jia; Wanrui Ma (Toxicology, 2024)

Density affects plant size in the Gobi Desert - Yonghua Li; Zhiming Xin; Bin Yao; Ruibing Duan; Xue Dong; Yanfeng Bao; Xinle Li; Yuan Ma; Yaru Huang; Fengmin Luo; Xing Li; Xu Wei; et al. (Science of The Total Environment, 2024)

Mixed sowing of Feed rape and Vicia villosa can substitute nitrogen fertilizer to improve soil multifunctionality in the Hetao irrigation District - Ru Yu; Hongyuan Zhang; Fangdi Chang; Jiashen Song; Jing Wang; Xiquan Wang; Zhengrong Kan; Na Zhao; Xiaohong Li; Jun Ma; Yuyi Li (CATENA, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Peduncle collision-free grasping based on deep reinforcement learning for tomato harvesting robot - Yajun Li; Qingchun Feng; Yifan Zhang; Chuanlang Peng; Yuhang Ma; Cheng Liu; Mengfei Ru; Jiahui Sun; Chunjiang Zhao (Computers and Electronics in Agriculture, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Corrigendum to “Silica nanoparticles promote oxLDL-induced macrophage lipid accumulation and apoptosis via endoplasmic reticulum stress signaling” [Sci. Total Environ., 631-632 (2018): 570-579] - Caixia Guo; Ru Ma; Xiaoying Liu; Tian Chen; Yang Li; Yang Yu; Junchao Duan; Xianqing Zhou; Yanbo Li; Zhiwei Sun (Science of The Total Environment, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

Insights into greenhouse gas emissions from a wastewater treatment plant in vulnerable water areas of China - Jiemiao Ma; Xiaojing Ni; Chen Cai; Yuewu Da; Kan Hu; Ru Guo; Jia Liu; Kaiming Peng; Erwu Liu; Xiangfeng Huang (Science of The Total Environment, 2023)

Paleoproterozoic crustal evolution of the Tarim Craton, NW China: Constraints from geochronology and geochemistry of orthogneisses and granitic veins in the Xingdi region of the Quruqtagh Block - Xiao-Hui Sun; Xiang Li; Ru-Xiong Lei; Matthew J. Brzozowski; Hua-Dong Ma; Wei Li; Li-Ming Xiong; Ming-Yi Xia; Chang-Zhi Wu (Precambrian Research, 2023)

Polystyrene grafted hollow layered double hydroxides (NiCo-LDH@PS) as solid phase microextraction coating for enhanced capture of polycyclic aromatic hydrocarbons - Xuemei Wang; Jie Zhang; Zhen Zhang; Jing Ru; Yuan Ma; Jingwei Liu; Xinzhen Du; Xiaoquan Lu (Journal of Environmental Chemical Engineering, 2023)

Co-delivery of curcumin and quercetin in the bilayer structure based on complex coacervation - Le Ma; Chun-Ru Su; Shi-Ying Li; Shan He; Anindya Nag; Yang Yuan (Food Hydrocolloids, 2023)

Organophosphate esters (OPEs) in a heavily polluted river in South China: Occurrence, spatiotemporal trends, sources, and phase distribution - Yi-Shan Liu; Hui-Ru Li; Zhi-Lang Lao; Sheng-Tao Ma; Zi-Cong Liao; Ai-Min Song; Ming-Yang Liu; You-Sheng Liu; Guang-Guo Ying (Environmental Pollution, 2023)

Advances in understanding entire process of medium chain carboxylic acid production from organic wastes via chain elongation - Qingyan Wang; Nan Yang; Yajing Cai; Ru Zhang; Yan Wu; Weifang Ma; Chuan Fu; Panyue Zhang; Guangming Zhang (Chemosphere, 2023)

Deep insights into the population shift of n-DAMO and Anammox in granular sludge: From sidestream to mainstream - Sheng-Qiang Fan; Wan-Ru Wen; Guo-Jun Xie; Yang Lu; Bing-Feng Liu; De-Feng Xing; Jun Ma; Nan-Qi Ren (Water Research, 2023)

Recent understanding of stress response on muscle quality of fish: From the perspective of industrial chain - Tonghao Zhang; Liangzi Zhang; Tao Yin; Juan You; Ru Liu; Qilin Huang; Liu Shi; Lan Wang; Tao Liao; Weisheng Wang; Huawei Ma (Trends in Food Science & Technology, 2023)

Metagenomic analysis reveals the efficient digestion mechanism of corn stover in Angus bull rumen: Microbial community succession, CAZyme composition and functional gene expression - Jinsong Liang; Jianning Chang; Ru Zhang; Wei Fang; Le Chen; Weifang Ma; Yajie Zhang; Wenjing Yang; Yuehan Li; Panyue Zhang; Guangming Zhang (Chemosphere, 2023)

Exploration of using acoustic vibration technology to non-destructively detect moldy kernels of in-shell hickory nuts (Carya cathayensis Sarg.) - Qing-li Han; Bai-xue Long; Xue-jun Yan; Wu Wang; Feng-ru Liu; Xue Chen; Fei Ma (Computers and Electronics in Agriculture, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Iron reduction in composting environment synergized with quinone redox cycling drives humification and free radical production from humic substances - Ru Sun; Mengxin Fu; Liangcai Ma; Yucheng Zhou; Qunliang Li (Bioresource Technology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

CAT Interruption as a Protective Factor in Chinese Patients with Spinocerebellar Ataxia Type 1 - Ya-Ru Shao; Jin-Yang Yu; Yin Ma; Yi Dong; Zhi-Ying Wu (The Cerebellum, 2023)

Silica nanoparticles promoted pro-inflammatory macrophage and foam cell transformation via ROS/PPARγ/NF-κB signaling - Caixia Guo; Xinying Zhao; Ru Ma; Lingnan Zhu; Yueyue Chen; Zhu Yang; Zongwei Cai; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Chronology analysis of huge landslide based on ESR dating materials on sliding face in carbonate areas of south eastern Tibet - Chun-Ru Liu; Ying-Ying Tian; Hao Ji; Xi Ma; Chuan-Yi Wei; Jia-Xiang Dang; Gong-Ming Yin; Yong-Sheng Zhou; Ren-Mao Yuan (Quaternary Geochronology, 2023)

Surfactants/citric acid catalyzed hydrothermal carbonization of pomelo peel for solid fuels: Conversion mechanism and combustion performance - Ru Ma; Sandile Fakudze; Shuai Liu; Yingyuan Wei; Jianqiang Chen; Jiangang Han; Chen Wang; Jiaxin Wang (Fuel, 2023)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Automatic back analysis of mechanical parameters using block discrete element method and PSO algorithm - Hang-Sheng Ma; Huan-Ling Wang; Ru-Bin Wang; Qing-Xiang Meng; Lan-Lan Yang (European Journal of Environmental and Civil Engineering, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

When things get MESI: The Manipulation Experiments Synthesis Initiative—A coordinated effort to synthesize terrestrial global change experiments - Kevin Van Sundert; Sebastian Leuzinger; Martin K.‐F. Bader; Scott X. Chang; Martin G. De Kauwe; Jeffrey S. Dukes; J. Adam Langley; Zilong Ma; Bertold Mariën; Simon Reynaert; Jingyi Ru; Jian Song; et al. (Global Change Biology, 2023)
Responses of the terrestrial biosphere to rapidly changing environmental conditions are a major source of uncertainty in climate projections. In an effort to reduce this uncertainty, a wide range of global change experiments have been conducted that mimic future conditions in terrestrial ecosystems, manipulating CO 2 , temperature, and nutrient and water availability. Syntheses of results across experiments provide a more general sense of ecosystem responses to global change, and help to discern the influence of background conditions such as climate and vegetation type in determining global change responses. Several independent syntheses of published data have yielded distinct databases for specific objectives. Such parallel, uncoordinated initiatives carry the risk of producing redundant data collection efforts and have led to contrasting outcomes without clarifying the underlying reason for divergence. These problems could be avoided by creating a publicly available, updatable, curated database. Here, we report on a global effort to collect and curate 57,089 treatment responses across 3644 manipulation experiments at 1145 sites, simulating elevated CO 2 , warming, nutrient addition, and precipitation changes. In the resulting Manipulation Experiments Synthesis Initiative (MESI) database, effects of experimental global change drivers on carbon and nutrient cycles are included, as well as ancillary data such as background climate, vegetation type, treatment magnitude, duration, and, unique to our database, measured soil properties. Our analysis of the database indicates that most experiments are short term (one or few growing seasons), conducted in the USA, Europe, or China, and that the most abundantly reported variable is aboveground biomass. We provide the most comprehensive multifactor global change database to date, enabling the research community to tackle open research questions, vital to global policymaking. The MESI database, freely accessible at doi.org/10.5281/zenodo.7153253 , opens new avenues for model evaluation and synthesis‐based understanding of how global change affects terrestrial biomes. We welcome contributions to the database on GitHub.

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Proteomic profiling reveals dysregulated mitochondrial complex subunits responsible for myocardial toxicity induced by SiNPs - Xinying Zhao; Hailin Xu; Yan Li; Ru Ma; Yi Qi; Min Zhang; Caixia Guo; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Quinone redox cycling drives lignocellulose depolymerization and degradation in composting environments based on metagenomics analysis - Ru Sun; Ziyi Cao; Xiaoli Wen; Liangcai Ma; Yucheng Zhou; Jixuan Li; Mengxin Fu; Pengfei Zhu; Kecheng Li; Qunliang Li (Science of The Total Environment, 2023)

Lycopsid Lepacyclotes Emmons from the Middle Triassic of the Ordos Basin, North China and reviews of the genus - Shenghui Deng; Yuanzheng Lu; Ru Fan; Zhong Luo; Xueying Ma; Dan Lyu; Yanqi Sun (Review of Palaeobotany and Palynology, 2023)

Comparison of biochemical composition, nutritional quality, and metals concentrations between males and females of three different Crassostrea sp. - Yanping Qin; Ru Li; Qingliang Liao; Gongpengyang Shi; Yinyin Zhou; Weitao Wan; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Food Chemistry, 2023)

Narrowing fossil fuel consumption in the Indian road transport sector towards reaching carbon neutrality - M.S. Hossain; Yan Ru Fang; Teng Ma; Chen Huang; Wei Peng; Johannes Urpelainen; Chetan Hebbale; Hancheng Dai (Energy Policy, 2023)

Transcriptome‐based analyses of adaptive divergence between two closely related spruce species on the Qinghai–Tibet plateau and adjacent regions - Shuo Feng; Wei Wan; Yang Li; DongLei Wang; Guangpeng Ren; Tao Ma; Dafu Ru (Molecular Ecology, 2023)
Speciation among populations connected by gene flow is driven by adaptation to different environments, but underlying gene–environment associations remain largely unknown. Here, 162 individuals from 32 populations were sampled to obtain 191,648 independent single nucleotide polymorphisms (SNPs) across the genomes of two closely related spruce species, Picea asperata and Picea crassifolia , which occur on the Qinghai–Tibet Plateau and in surrounding regions. Using the SNP data set, genotype–environment associations and demographic modelling were used to examine local adaptation and genetic divergence between these two species. While morphologically similar, the two Picea species were genetically differentiated in multiple analyses. These species diverged despite continuous gene flow, and their initial divergence was dated back to the late Quaternary. The effective population sizes of both species have expanded since their divergence, as confirmed by niche distribution simulations. A total of 6365 genes were associated with the tested environmental variables; of these, 41 were positively selected in P. asperata and were mainly associated with temperature, while 83 were positively selected in P. crassifolia and were primarily associated with precipitation. These results deepen our understanding of the adaptive divergence and demographic histories of these two spruce species and highlight the importance of genomic data in deciphering the environmental selection underlying Quaternary interspecific divergence.

PITPNC1 promotes the thermogenesis of brown adipose tissue under acute cold exposure - Guoqing Tang; Chengxin Ma; Liangkui Li; Shaoyan Zhang; Fengsheng Li; Jin Wu; Yesheng Yin; Qing Zhu; Yan Liang; Ru Wang; He Huang; Tong-Jin Zhao; et al. (Science China Life Sciences, 2022)
Brown adipose tissue (BAT) plays an essential role in non-shivering thermogenesis. The phosphatidylinositol transfer protein, cytoplasmic 1 (PITPNC1) is identified as a lipid transporter that reciprocally transfers phospholipids between intracellular membrane structures. However, the physiological significance of PITPNC1 and its regulatory mechanism remain unclear. Here, we demonstrate that PITPNC1 is a key player in thermogenesis of BAT. While Pitpnc1 −/− mice do not differ with wildtype mice in body weight and insulin sensitivity on either chow or high-fat diet, they develop hypothermia when subjected to acute cold exposure at 4°C. The Pitpnc1 −/− brown adipocytes exhibit defective β-oxidation and abnormal thermogenesis-related metabolism pathways in mitochondria. The deficiency of lipid mobilization in Pitpnc1 −/− brown adipocytes might be the result of excessive accumulation of phosphatidylcholine and a reduction of phosphatidic acid. Our findings have uncovered significant roles of PITPNC1 in mitochondrial phospholipid homeostasis and BAT thermogenesis.

High- and low-temperature fracture behavior of pervious asphalt mixtures under different freeze–thaw cycles based on acoustic emission technique - Tianmin Wang; Yu Chen; Changqi Zhu; Haifeng Liu; Chenghao Ma; Xing Wang; Ru Qu (Arabian Journal of Geosciences, 2022)

ACOT7 protects epidermal stem cells against lipid peroxidation - Guang Zhang; Jiaxu Ma; Zhenjie Wu; Guoqi Cao; Chunyan Liu; Ru Song; Rui Sun; Aoyu Chen; Yibing Wang; Siyuan Yin (In Vitro Cellular & Developmental Biology - Animal, 2022)
Epidermal stem cells (ESCs) are critical for skin regeneration and repair. Previous studies have shown that ESCs are susceptible to oxidative stress, which in turn leads to lipid peroxidation and affects skin repair. Our study aims to explore how ESCs resist lipid peroxidation. By performing proteomics analysis, we found that the expression of Acyl-CoA thioesterase 7 (ACOT7) was positively correlated with the concentration of transferrin. Overexpression adenovirus vectors of ACOT7 were constructed and transfected into ESCs. Levels of lipid peroxidation by flow cytometry, cell viabilities, and MDA levels were measured. The results revealed that ACOT7 could inhibit lipid peroxidation, reduce the level of malondialdehyde (MDA), and improve the survival rate of ESCs induced by H 2 O 2 , Erastin, and RSL3. Our data suggest that ACOT7 has an effect on protecting ESCs against iron-dependent lipid peroxidation.

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Analyzing the mechanism of nitrous oxide production in aerobic phase of anoxic/aerobic sequential batch reactor from the perspective of key enzymes - Rui Yang; Lin-jiang Yuan; Ru Wang; Zhi-xian He; Lin Lei; Yan-chen Ma (Environmental Science and Pollution Research, 2022)

Increased precipitation and nitrogen addition accelerate the temporal increase in soil respiration during 8‐year old‐field grassland succession - Jiajia Zhang; Jingyi Ru; Jian Song; Heng Li; Xiaoming Li; Yafei Ma; Zheng Li; Yuanfeng Hao; Zhensheng Chi; Dafeng Hui; Shiqiang Wan (Global Change Biology, 2022)
Ecological succession after disturbance plays a vital role in influencing ecosystem structure and functioning. However, how global change factors regulate ecosystem carbon (C) cycling in successional plant communities remains largely elusive. As part of an 8‐year (2012–2019) manipulative experiment, this study was designed to examine the responses of soil respiration and its heterotrophic component to simulated increases in precipitation and atmospheric nitrogen (N) deposition in an old‐field grassland undergoing secondary succession. Over the 8‐year experimental period, increased precipitation stimulated soil respiration by 11.6%, but did not affect soil heterotrophic respiration. Nitrogen addition increased both soil respiration (5.1%) and heterotrophic respiration (6.2%). Soil respiration and heterotrophic respiration linearly increased with time in the control plots, resulting from changes in soil moisture and shifts of plant community composition from grass–forb codominance to grass dominance in this old‐field grassland. Compared to the control, increased precipitation significantly strengthened the temporal increase in soil respiration through stimulating belowground net primary productivity. By contrast, N addition accelerated temporal increases in both soil respiration and its heterotrophic component by driving plant community shifts and thus stimulating soil organic C. Our findings indicate that increases in water and N availabilities may accelerate soil C release during old‐field grassland succession and reduce their potential positive impacts on soil C accumulation under future climate change scenarios.

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

Carbon, oxygen and strontium isotopes of the Mesoproterozoic Jixian System （1.6-1.4 Ga）in the southern margin of the North China Craton and the geological implications - Cong Tan; Yuanzheng Lu; Xin Li; Haonan Song; Dan Lv; Xueying Ma; Ru Fan; Shenghui Deng (International Geology Review, 2021)

Evolutionary origin of a tetraploid Allium species on the Qinghai–Tibet Plateau - Minjie Li; Zeyu Zheng; Juncheng Liu; Yongzhi Yang; Guangpeng Ren; Dafu Ru; Shangzhe Zhang; Xin Du; Tao Ma; Richard Milne; Jianquan Liu (Molecular Ecology, 2021)
Extinct taxa may be detectable if they were ancestors to extant hybrid species, which retain their genetic signature. In this study, we combined phylogenomics, population genetics and fluorescence in situ hybridization (GISH and FISH) analyses to trace the origin of the alpine tetraploid Allium tetraploideum (2 n = 4 x = 32), one of the five known members in the subgenus Cyathophora . We found that A. tetraploideum was an obvious allotetrapoploid derived from ancestors including at least two closely related diploid species, A. farreri and A. cyathophorum , from which it differs by multiple ecological and genomic attributes. However, these two species cannot account for the full genome of A. tetraploideum , indicating that at least one extinct diploid is also involved in its ancestry. Furthermore, A. tetraploideum appears to have arisen via homoploid hybrid speciation (HHS) from two extinct allotetraploid parents, which derived in turn from the aforementioned diploids. Other modes of origin were possible, but all were even more complex and involved additional extinct ancestors. Our study together highlights how some polyploid species might have very complex origins, involving both HHS and polyploid speciation and also extinct ancestors.

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

Prediction of Metabolic Disorders Using NMR-Based Metabolomics: The Shanghai Changfeng Study - Qi Wu; Qing-xia Huang; Hai-luan Zeng; Shuai Ma; Huan-dong Lin; Ming-feng Xia; Hui-ru Tang; Xin Gao (Phenomics, 2021)

Biomimetic Au nanodot synthesis using Escherichia coli secretion and interaction with α-ketoglutaric acid - Xiaoxiao Xie; Xiaoli Yang; Yi Chang; Xiangli Ru; Xiaoming Ma; Lin Yang (Science China Life Sciences, 2021)

Nonadditive and Legacy Effects of Spring and Autumn Warming on Soil Respiration in an Old-Field Grassland - Shijie Ning; Jian Song; Jingyi Ru; Zhenxing Zhou; Jiajia Zhang; Xianghui Liu; Yan Hui; Yafei Ma; Shiqiang Wan (Ecosystems, 2021)

Factors Associated with Intergenerational Instability of ATXN3 CAG Repeat and Genetic Anticipation in Chinese Patients with Spinocerebellar Ataxia Type 3 - Yi-Chu Du; Yin Ma; Ya-Ru Shao; Shi-Rui Gan; Yi Dong; Zhi-Ying Wu (The Cerebellum, 2020)

Cadmium phytotoxicity, related physiological changes in Pontederia cordata: antioxidative, osmoregulatory substances, phytochelatins, photosynthesis, and chlorophyll fluorescence - Jian-pan Xin; SiSi Ma; Chu Zhao; Yan Li; Ru-nan Tian (Environmental Science and Pollution Research, 2020)

The neural mechanisms of immediate and follow-up of the treatment effect of hypnosis on smoking craving - Xiaoming Li; Lijun Chen; Ru Ma; Haibao Wang; Li Wan; Junjie Bu; Wei Hong; Wanwan Lv; Yihong Yang; Hengyi Rao; Xiaochu Zhang (Brain Imaging and Behavior, 2020)

Effects of oxygen tension on the microbial community and functional gene expression of aerobic methane oxidation coupled to denitrification systems - Yi-Xuan Chu; Ruo-Chan Ma; Jing Wang; Jia-Tian Zhu; Ya-Ru Kang; Ruo He (Environmental Science and Pollution Research, 2020)

Influence of Vitamin D Status and Mechanical Loading on the Morphometric and Mechanical Properties of the Mouse Tibia - Yong-Tao Lu; Zhen-Tao Cui; Han-Xing Zhu; Ru-Kun Ma; Cheng-Wei Wu (Journal of Medical and Biological Engineering, 2019)

Dispersion and attenuation of compressional waves in tight oil reservoirs: Experiments and simulations - Ru-Peng Ma; Jing Ba; José Maria Carcione; Xin Zhou; Fan Li (Applied Geophysics, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Subdivision and age of the Yanchang Formation and the Middle/Upper Triassic boundary in Ordos Basin, North China - Shenghui Deng; Yuanzheng Lu; Zhong Luo; Ru Fan; Xin Li; Yi Zhao; Xueying Ma; Rukai Zhu; Jingwei Cui (Science China Earth Sciences, 2018)

Development of homologous enzyme-linked immunosorbent assays to quantify two forms of vitellogenin in guppy (Poecilia reticulata) - Mingyi Zheng; Jun Wang; Zhenzhong Zhang; Shuwei Ma; Shaoguo Ru (Environmental Science and Pollution Research, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Absorption and subcellular distribution of cadmium in tea plant (Camellia sinensis cv. “Shuchazao”) - De-ju Cao; Xun Yang; Geng Geng; Xiao-chun Wan; Ru-xiao Ma; Qian Zhang; Yue-gan Liang (Environmental Science and Pollution Research, 2018)

Differential Inhibition of Nav1.7 and Neuropathic Pain by Hybridoma-Produced and Recombinant Monoclonal Antibodies that Target Nav1.7 - Sangsu Bang; Jiho Yoo; Xingrui Gong; Di Liu; Qingjian Han; Xin Luo; Wonseok Chang; Gang Chen; Sang-Taek Im; Yong Ho Kim; Judith A. Strong; Ma-Zhong Zhang; et al. (Neuroscience Bulletin, 2018)

Retraction Note To: VEGF Silencing Inhibits Human Osteosarcoma Angiogenesis and Promotes Cell Apoptosis via PI3K/AKT Signaling Pathway - Jian Zhao; Zi-Ru Zhang; Na Zhao; Bao-An Ma; Qing-Yu Fan (Cell Biochemistry and Biophysics, 2017)

Assessment of Photodegradation of Herbicide Prometryn in Soil - Chen Jiang; Xue Jing Li; Ya Ru Wang; Li Ya Ma; Ya Kun Wang; Yi Chen Lu; Hong Yang (Water, Air, & Soil Pollution, 2017)

Altered Resting-State Signals in Patients with Acute Stroke In or Under the Thalamus - Lijun Chen; Chuanfu Li; Jian Zhai; Anqin Wang; Qin Song; Ying Liu; Ru Ma; Long Han; Yamikani Ndasauka; Xiaoming Li; Hai Li; Xiaochu Zhang (Neuroscience Bulletin, 2016)

A new method for the stability analysis of geosynthetic-reinforced slopes - Fei Song; Ru-yi Chen; Li-qiu Ma; Geng-ren Cao (Journal of Mountain Science, 2016)

Induced growth promotion and higher salt tolerance in the halophyte grass Puccinellia tenuiflora by beneficial rhizobacteria - Shu-Qi Niu; Hui-Ru Li; Paul W. Paré; Mina Aziz; Suo-Min Wang; Huazhong Shi; Jing Li; Qing-Qing Han; Shi-Qian Guo; Jian Li; Qiang Guo; Qing Ma; et al. (Plant and Soil, 2016)

Mild Hypothermia Combined with Hydrogen Sulfide Treatment During Resuscitation Reduces Hippocampal Neuron Apoptosis Via NR2A, NR2B, and PI3K-Akt Signaling in a Rat Model of Cerebral Ischemia-Reperfusion Injury - Hai-Bin Dai; Miao-Miao Xu; Jia Lv; Xiang-Jun Ji; Si-Hai Zhu; Ru-Meng Ma; Xiao-Lei Miao; Man-Lin Duan (Molecular Neurobiology, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

Silencing of dehydrin CaDHN1 diminishes tolerance to multiple abiotic stresses in Capsicum annuum L. - Ru-gang Chen; Hua Jing; Wei-li Guo; Shu-Bin Wang; Fang Ma; Bao-Gui Pan; Zhen-Hui Gong (Plant Cell Reports, 2015)

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

RETRACTED ARTICLE: VEGF Silencing Inhibits Human Osteosarcoma Angiogenesis and Promotes Cell Apoptosis via PI3K/AKT Signaling Pathway - Jian Zhao; Zi-Ru Zhang; Na Zhao; Bao-An Ma; Qing-Yu Fan (Cell Biochemistry and Biophysics, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Association between vitamin D receptor gene polymorphism (TaqI) and obesity in Chinese population - HUI-RU FAN; LI-QUN LIN; HAO MA; YING LI; CHANG-HAO SUN (Journal of Genetics, 2015)

Effect of microRNA-203 on tumor growth in human hypopharyngeal squamous cell carcinoma - Ru Wang; Jugao Fang; Hongzhi Ma; Lin Feng; Meng Lian; Fan Yang; Haizhou Wang; Qi Wang; Xiaohong Chen (Molecular and Cellular Biochemistry, 2015)

Using fluorescence spectroscopy coupled with chemometric analysis to investigate the origin, composition, and dynamics of dissolved organic matter in leachate-polluted groundwater - Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Lei Wang; Yan Ma; Dong-Yu Cui; Wen-Bing Tan (Environmental Science and Pollution Research, 2015)

Ameliorative effects of Bacillus subtilis ANSB01G on zearalenone toxicosis in pre-pubertal female gilts - Lihong Zhao; Yuanpei Lei; Yinghui Bao; Ru Jia; Qiugang Ma; Jianyun Zhang; Jun Chen; Cheng Ji (Food Additives & Contaminants: Part A, 2015)

Distribution and ecological risk assessment of HCHs and DDTs in surface seawater and sediment of the mariculture area of Jincheng Bay, China - Yanbing Hu; Shan Sun; Xiukai Song; Jianxin Ma; Shaoguo Ru (Journal of Ocean University of China, 2015)

Inactivation of FoxM1 transcription factor contributes to curcumin-induced inhibition of survival, angiogenesis, and chemosensitivity in acute myeloid leukemia cells - Jing-ru Zhang; Fei Lu; Ting Lu; Wen-hao Dong; Peng Li; Na Liu; Dao-xin Ma; Chun-yan Ji (Journal of Molecular Medicine, 2014)

The Recovery Process of Mice Tracheal Epithelium Injured by 5-FU and Its Microarray Analysis - Jing-Ru Zhang; Nan Song; Xin-Shan Jia; Shan-Liang Sun; Xiao-Bo Ma; En-Hua Wang (Cell Biochemistry and Biophysics, 2014)

Rapid development of tissue bank achieved by International Atomic Energy Agency (IAEA) Tissue Banking Programme in China - Yu-Min Zhang; Jian-Ru Wang; Nai-Li Zhang; Xiao-Ming Liu; Mo Zhou; Shao-Ying Ma; Ting Yang; Bao-Xing Li (Cell and Tissue Banking, 2014)

Etanercept in the Treatment of Intestinal Behcet’s Disease - Dan Ma; Chao-Jun Zhang; Ru-Peng Wang; Lie Wang; Hua Yang (Cell Biochemistry and Biophysics, 2014)

Protective effect of hydrogen-rich saline on ischemia/reperfusion injury in rat skin flap - Ling Zhao; You-bin Wang; Shi-rui Qin; Xue-mei Ma; Xue-jun Sun; Ming-lian Wang; Ru-gang Zhong (Journal of Zhejiang University-SCIENCE B, 2013)

Molecular cloning, expression profiles and subcellular localization of cyclin B in ovary of the mud crab, Scylla paramamosain - Wen-Xing Li; Hui-Yang Huang; Jing-Ru Huang; Jin-Jin Yu; Jun Ma; Hai-Hui Ye (Genes & Genomics, 2013)

Analysis of average standardized SSR allele size supports domestication of soybean along the Yellow River - Ying-hui Li; Chen Zhang; Marinus J. M. Smulders; Wei Li; Yan-song Ma; Qu Xu; Ru-zhen Chang; Li-juan Qiu (Genetic Resources and Crop Evolution, 2013)

Culture-independent characterization of the autochthonous gut microbiota of grouper Epinephelus coioides following the administration of probiotic Enterococcus faecium - Yun-Zhang Sun; Hong-Ling Yang; Ru-Long Ma; Kun-Peng Huang; Ji-Dan Ye (Aquaculture International, 2012)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

Establishment of a transgene expression system for the marine microalga Schizochytrium by 18S rDNA-targeted homologous recombination - Ru-Bin Cheng; Xiang-Zhi Lin; Zhao-Kai Wang; Shan-Jun Yang; Hui Rong; Yong Ma (World Journal of Microbiology and Biotechnology, 2011)

PTEN status is related to cell proliferation and self-renewal independent of CD133 phenotype in the glioma-initiating cells - Ru-Bin Cheng; Rui-Juan Ma; Zhao-Kai Wang; Shan-Jun Yang; Xiang-Zhi Lin; Hui Rong; Yong Ma (Molecular and Cellular Biochemistry, 2011)

Genetic relationships between resistances to Fusarium head blight and crown rot in bread wheat (Triticum aestivum L.) - Hao Bing Li; Guo Qiang Xie; Jun Ma; Gui Ru Liu; Shu Min Wen; Tomohiro Ban; Sukumar Chakraborty; Chun Ji Liu (Theoretical and Applied Genetics, 2010)

Phthalic Acid Induces Oxidative Stress and Alters the Activity of Some Antioxidant Enzymes in Roots of Malus prunifolia - Ru Bai; Fengwang Ma; Dong Liang; Xin Zhao (Journal of Chemical Ecology, 2009)

The Influence of Center of Rotation on the Assessment of Trabecular Bone Densitometric and Structural Properties - Zhi-Feng Sheng; Ru-Chun Dai; Xian-Ping Wu; Yu-Lin Ma; Kang Xu; Yu-Hai Zhang; Ye-Bin Jiang; Er-Yuan Liao (Annals of Biomedical Engineering, 2008)

Improved biodesulfurization of hydrodesulfurized diesel oil using Rhodococcus erythropolis and Gordonia sp. - Guo-Qiang Li; Shan-Shan Li; Shi-Wei Qu; Qing-Kun Liu; Ting Ma; Lin Zhu; Feng-Lai Liang; Ru-Lin Liu (Biotechnology Letters, 2008)

Protolith natures and U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) zircon ages of the metabasites in Hainan Island, South China: Implications for geodynamic evolution since the late Precambrian - De‐Ru Xu; Bin Xia; Peng‐Chun Li; Guang‐Hao Chen; Ci Ma; Yu‐Quan Zhang (Island Arc, 2007)
Metabasites within the Paleozoic volcanic‐clastic sedimentary sequences in Hainan Island, South China, show large differences not only in the nature of protoliths, but also in zircon U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) ages. The protoliths for the Tunchang area metabasites have intraoceanic arc geochemical affinities. In the east‐central island gabbroic to diabasic rocks and pillow lavas are also present, while the Bangxi area metabasites with back‐arc geochemical affinities in the northwest island consist of basaltic, gabbroic and/or picritic rocks. Three types of zircon domains/crystals in the Tunchang area metabasites are defined. Type 1 is comagmatic and yields concordant to approximately concordant 206 Pb/238 U ages ranging from 442.1 ± 13.7 Ma to 514.3 ± 30.2 Ma with a weighted U‐Pb mean age of 445 ± 10 Ma. Type 2 is inherited and yields a weighted 207 Pb/206 Pb mean age of 2488.1 ± 8.3 Ma. Type 3 is magmatic with a 207 Pb/206 Pb age of ca 1450 Ma. Magmatic zircons in the Bangxi area metabasites yield a weighted U‐Pb mean age of 269 ± 4 Ma. We suggest 450 Ma is the minimum age for crystallization of protoliths of the Tunchang area metabasites, because the age range of ca 440–514 Ma probably corresponds to both the time of igneous crystallization and the high‐temperature overprint. The presence of abundant inherited zircons strongly favors derivation of these rocks from a NMORB‐like mantle proximal to continental crust. A protolith age of ca 270 Ma for the Bangxi area metabasites probably records expansion of an epircontinental back‐arc basin and subsequent generation of a small oceanic basin. The presence of ophiolitic rocks with an age of ca 450 Ma, not only in Hainan Island, but also in the Yangtze block, highlights the fact that the South China Caledonian Orogeny was not intracontinental in nature, but characterized by an ocean‐related event.

Hypoxic postconditioning enhances the survival and inhibits apoptosis of cardiomyocytes following reoxygenation: role of peroxynitrite formation - Hai-Chang Wang; Hai-Feng Zhang; Wen-Yi Guo; Hui Su; Kun-Ru Zhang; Qiu-Xia Li; Wenli Yan; Xin L. Ma; Bernard L. Lopez; Theodore A. Christopher; Feng Gao (Apoptosis, 2006)

Theoretical studies on the mechanism of primary electron transfer in the photosynthetic reaction center of Rhodobacter sphaeroides - Hong Xu; Ru-Bo Zhang; Shu-Hua Ma; Zheng-Wang Qu; Xing-Kang Zhang; Qi-Yuan Zhang (Photosynthesis Research, 2002)

Estimation of atmospheric input of mercury to South Lake and Jingyue Pool - Feng-man Fang; Qi-chao Wang; Zhuang-wei Ma; Ru-hai Liu; Yu-hong Cao (Chinese Geographical Science, 2002)